Study of flavor dependence of the baryon-to-meson ratio in proton-proton collisions at √s=13 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; Nath, Abhishek; et al. (Physical review, 2023)
The production cross sections of D0 and Λ+c hadrons originating from beauty-hadron decays (i.e., nonprompt) were measured for the first time at midrapidity (|𝑦|<0.5) by the ALICE Collaboration in proton-proton collisions at a center-of-mass energy √𝑠=13 TeV. They are described within uncertainties by perturbative QCD calculations employing the fragmentation fractions of beauty quarks to baryons measured at forward rapidity by the LHCb Collaboration. The b⁢¯b production cross section per unit of rapidity at midrapidity, estimated from these measurements, is d⁢𝜎b⁢¯b/d⁢𝑦||𝑦|<0.5=83.1±3.5⁢(stat)±5.4⁢(syst)+12.3−3.2⁢(extrap) μ⁢b. The baryon-to-meson ratios are computed to investigate the hadronization mechanism of beauty quarks. The nonprompt Λ+c/D0 production ratio has a similar trend to the one measured for the promptly produced charmed particles and to the p/𝜋+ and Λ/K0S ratios, suggesting a similar baryon-formation mechanism among light, strange, charm, and beauty hadrons. The 𝑝T -integrated nonprompt Λ+c/D0 ratio is found to be significantly higher than the one measured in e+⁢e− collisions.
Gesehen am 11.07.2024
ALICE Collaboration: S. Acharya, V. Angelov, A. Berdnikova, L. Bergmann, A.G. Bórquez Carcamo, J. Crkovská, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, M. Völkl, B. Windelband, A. Yüncü, F. Zanone, [und 1030 weitere]